Precision nitrogen management practices in wheat influences nutrient uptake and their use efficiencies and fertility status of soil under conservation agriculture - Mohanty, S.K.; Jat, S.L.; Parihar, C.M.; Singh, A.K.; Sharma, S.; Saveipune, D.; ., Sandhya; Kuri, B.R. (Annals of Agricultural Research, 2016)
A field experiment was conducted at New Delhi during Rabi season of 2012-13 to study the precisionnitrogen management in wheat grown under conservation agriculture. The experiment was laidout in a factorial randomized block design with twenty treatment combinations four nutrientmanagement in preceding maize [absolute control, recommended dose of fertilizers (RDF), 50%RDF and site-specific nutrient management (SSNM)] and five precision N management practices inwheat [control, RDF, green seeker, SPAD and soil-test crop response (STCR)} in sandy loam soil.Amongst tested N management strategies; a saving of N by 9.5 and 30 kg with green seeker andSPAD, respectively while enhancement of 18.4 kg N/ha by STCR was found compared torecommended dose of fertilizers (RDF). N, P and K content and their uptake in grain, straw inwheat was significantly higher with STCR based nutrient management applied in wheat as well aswith nutrient expert based SSNM applied in maize as residual effect. The same trend was alsofollowed in case of protein content in wheat grain. However, the nutrient harvest index (NHI) of N,P and K was significantly higher under nutrient expert based SSNM applied in maize as residualeffect. Whereas, NHI of N and P was significantly higher with absolute control but NHI of K wasnot influenced by different precision N management practices. Soil ammonical and nitrateconcentration was significantly higher by STCR based nutrient management as well as with nutrientexpert based SSNM applied in maize as residual effect, however soil phosphate concentration wassignificantly higher with SPAD in wheat and 100% RDF as residual effect of nutrient managementin maize, respectively. Among different precision N management practices significantly higher Znconcentration was recorded with STCR, however Cu and Fe concentration was significantly higherwith 100% RDF and STCR, respectively.